The Principle of Limb Reconstruction—“One Walking, Two Lines, and Three Balances”: A Retrospective Analysis of Post‐Traumatic Lower Limb Deformity Correction - Jiancheng Zang; Fangyuan Wei; Lei Shi; Sihe Qin (Orthopaedic Surgery)
Objective The principles of limb reconstruction are crucial for treatment success, but there is no unified standard for complex limb deformities. The aim of this study was to analyze the characteristics of the cases of post‐traumatic lower limb deformity and explore the new principle of limb reconstruction. Method A retrospective analysis was conducted of 148 patients with post‐traumatic lower limb deformity who underwent surgery from May 1978 to December 2023; 85 were males (57.4%) and 63 were females (42.6%); 65 cases of left side (43.9%), 79 cases of right side(53.4%), and 4 cases were on both sides (2.7%), the average age was 24.64 years (5–69). There were 4 cases suffering hip deformities, 40 cases of femoral deformities, 18 cases from knee, 40 cases from tibiofibular, 93 cases of foot and ankle deformities, and some patients also had two or more types. All patients underwent surgical intervention in an average of 40.5 months (12–96) after injury. According to the evaluation of limb deformities, deformity correction and functional reconstruction with external fixation were implemented, following the principle of “one walking, two lines, and three balances.” The clinical evaluation adopts the criteria of Qinsihe lower limb deformity correction and functional reconstruction. Result 148 patients with post‐traumatic lower limb deformities were followed up for 40.9 (12–356) months. The main surgical procedures implemented were tendon lengthening and soft tissue release (84 cases), osteotomy (93 cases), joint fusion (30 cases), and tendon transposition (16 cases); there were multiple surgical procedures in some patients. Among them, 124 cases used external fixators for stress control and 27 cases used internal fixation, while 3 cases used plaster or brace. There were 5 wire reactions postoperatively, which improved after dressing change and oral antibiotics. There were 2 pin infections, which improved by pin removing. No surgical related deep infections occurred, and no surgical related neurovascular damage occurred. At the last follow‐up, all limb deformities were corrected, limb function improved, and the results of treatment was very satisfactory. According to Qinsihe evaluation criteria for lower limb deformities, 74 cases were excellent, 56 cases good, and 18 cases fair, with an excellent and good rate of 87.84%. Conclusion Stress control with external fixation is effective, safe, and controllable in correcting and reconstructing post‐traumatic lower limb deformities. The principle of “one walking, two lines, and three balances” plays an important role in the entire process of stress control limb reconstruction.